Curious George. Be my Valentine [videorecording (DVD)]. - Rey, H. A. (Hans Augusto), 1898-1977 (Curious George (Television program), 2018)
Kids will fall in love with the world's most mischievous monkey in six uplifting episodes. Join Curious George as he shares some Valentine's cheer, fixes a mix up at the zoo, entertains a sick friend, and lends a thoughtful hand to others.